Bimetallic MOFs (H3O)x[Cu(MF6)(pyrazine)2]·(4 − x)H2O (M = V4+, x = 0; M = Ga3+, x = 1): co-existence of ordered and disordered quantum spins in the V4+ system. Issue 85 (7th October 2016) - Manson, Jamie L.; Schlueter, John A.; Garrett, Kerry E.; Goddard, Paul A.; Lancaster, Tom; Möller, Johannes S.; Blundell, Stephen J.; Steele, Andrew J.; Franke, Isabel; Pratt, Francis L.; Singleton, John; Bendix, Jesper; et al.
Abstract : These bimetallic MOFs contain [Cu(pyz)2 ] 2+ sheets and MF6 n − octahedra whereby only the Cu(ii ) moments magnetically order. Abstract : The title compounds are bimetallic MOFs containing [Cu(pyz)2 ] 2+ square lattices linked by MF6 n − octahedra. In each, only the Cu 2+ spins exhibit long-range magnetic order below 3.5 K (M = V 4+ ) and 2.6 K (M = Ga 3+ ). The V 4+ spins remain disordered down to 0.5 K.